READING ERRORS ANALYSIS ON ENGLISH DYSLEXIC READERS - Sovian Nisa Nurul Baeti (University of Muhammadiyah Purwokerto, 2017)
This paper is to describe the patterns of reading errors made by a dyslexic child. The data of this research are obtained from YouTube channel of Stephen Round. On the video they were asked to read nine English children story books containing texts and pictures. The grade of the books began from lower grade book until on-level grade book relevant to their age. In conducting this research, the researcher used the four reading errors types from Savage, Stuart and Hill (2001) and other findings of two researchers as analysis tools for analyzing the reading errors produced by English children. Those are the research findings of Gupta (2006) and the research findings by Rabia (2004). Based on analysis, the result of this research revealed that the reading errors in the subject 1 are error sharing orthographic overlap, error preserving the initial phoneme, errors preserving the final phoneme, scaffolding errors, phonological errors, morphological errors, omission and addition. He is hard to make connection between the letters and its correspondent sound.